Prognostic value of circulating Chromogranin A in prostate cancer: a systematic review and meta-analysis - Tang, Xiaoying; Liu, Zhenyu; Song, Liangdong; Zhu, Huixuan; Su, Shuai; Wang, Delin (Frontiers in Oncology, 2025)
BackgroundThere are discrepancies between the results of different studies regarding the prognostic role of circulating Chromogranin A (CgA) in prostate cancer. Therefore, we conducted a meta-analysis of the available findings to explore the value of circulating Chromogranin A in the prognosis of prostate cancer.MethodsWe systematically searched the PubMed, Embase, Web of Science, Cochrane Library, and Clinical Trials databases for studies on the relationship between CgA and survival outcomes in prostate cancer from inception until December 2024, and we focused on articles detecting circulating CgA, with the primary endpoints of the studies being overall survival (OS), and progression-free survival (PFS).ResultsOf the 2049 articles retrieved, 10 articles met our inclusion criteria, involving a total of 1445 patients. Elevated circulating CgA was associated with poorer OS (HR=1.82, 95% CI: 1.38–2.41; p<0.001) and PFS (HR=2.04, 95% CI: 1.42–2.94; p<0.001). However, no correlation was found between post-treatment circulating CgA changes and OS (HR=0.95, 95% CI: 0.66–1.37; p=0.767).ConclusionCirculating CgA is a predictive marker of poor survival outcomes in prostate cancer However, the sample size of the current study is small and larger studies are needed to further validate this in the future.